On the Flow Stability in a Circular Cylinder based Open Volumetric Air Receiver for Solar Convective Furnace. (July 2018) - Singh, Gurveer; Chandra, Laltu
Abstract: The arid desert regions are considered for installing the concentrated solar thermal based systems owing to the available direct normal irradiance. For process heat applications, like the solar convective furnace that requires an air temperature of 750 K the open volumetric air receiver is preferred. Such innovative concepts are envisaged for achieving high thermal energy conversion efficiency. For the prolonged operation of the solar convective furnace system the stable flow is necessary. On the other hand, the thermally induced flow instability is reported in the open volumetric air receivers at a high temperature. This may limit the operating temperature range of a receiver. In this paper the flow stability analysis in a circular cylinder based open volumetric air receiver with the straight pores is presented. The findings allow expecting a stable flow regime in such an absorber pore at a high flux concentration and temperature.